A Novel Model for Data-Driven Smart Sustainable Cities of the Future: A Strategic Roadmap to Transformational Change in the Era of Big Data. Issue 1 (19th February 2021) - Bibri, Simon Elias; Krogstie, John
The conscious push for sustainable cities to be smarter and thus more sustainable in the era of big data is due to the problematicity surrounding their development planning approaches and operational management mechanisms, as well as the fragmentation of their designs and technologies. This has a clear bearing on their performance with respect to the contribution to and balancing of the goals of sustainability. This situation is compounded by the negative consequences of the expansion of urbanization, an irreversible global trend involving a multitude of environmental, social, economic, and spatial conditions that pose unprecedented challenges to policymakers and planners. The underlying argument is that more innovative solutions and sophisticated methods are needed to enable sustainable cities to tackle the kind of problems and complexities they embody. This in turn brings us to the question related to the weak connection between sustainable cities and smart cities as approaches as well as their extreme fragmentation as landscapes, both at the technical and policy levels. Therefore, sustainable cities need to embrace and leverage what smart cities have to offer so that they can optimize, enhance, and maintain their performance and thus achieve the desired outcomes of sustainability. This paper aims to develop a novel model for data-driven smart sustainable cities of the future, and in doing so, it provides a strategic planning process of transformative change towards sustainability. This model combines and integrates the prevailing paradigms of sustainable urbanism and the emerging paradigms of smart urbanism —based on the outcomes of the four case studies conducted on compact cities, eco-cities, data–driven smart cities, and environmentally data-driven smart sustainable cities. As the core of this aggregate model is how to bring about the different forms of infrastructural transformations needed to reach a vision of a sustainable future in the era of big data. Especially, it has become feasible to attain important improvements and advancements of sustainability by amalgamating sustainable cities and smart cities thanks to the proven role of advanced ICT and the untapped potential of data-driven technologies.